All that Glitters Is Wine? Viticultural Capitalists and the Creation of Britain’s Colonial Wine Industry - Davis, Chelsea (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2023)
The mineral revolutions of the nineteenth century served as a turning point in the colonial wine industries of South Australia and the Cape Colony. The discovery of gold and diamonds not only facilitated early efforts of industrialization, but equally created a class of “viticultural capitalists,” meaning settler colonialists who would invest their wealth into wine. This article will examine two case studies of viticultural capitalists who consolidated the processes of colonial wine production in the British Empire. These white settlers cultivated a space for corporate expansion, political “say” in management of each colony, and access to growing social and economic networks, which they used to import vines, technologies, ideas, and even people. Such privileges served to isolate small winegrowers and exploit viticultural labourers, especially individuals of colour. These viticultural capitalists and the creation of large-scale wine companies sought to transform wine into a colonial commodity for the empire.